2022
DOI: 10.1111/jcpe.13647
|View full text |Cite
|
Sign up to set email alerts
|

Ipriflavone suppresses NLRP3 inflammasome activation in host response to biomaterials and promotes early bone healing

Abstract: Aim: Emerging studies have shown that immune response to biomaterial implants plays a central role in bone healing. Ipriflavone is clinically used for osteoporosis.However, the mechanism of ipriflavone in immune response to implants in early stages of osseointegration remains unclear. In this study, we aimed to investigate the potential role of ipriflavone in early bone healing process and uncover the underlying mechanism. Materials and Methods:We carried out histological examination as well as analysis of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Chen et al. ( 2022 ) investigated the early inflammatory response to titanium screws in bone, and concluded that the administration of ipriflavone, a natural isoflavone, decreased the activation of the NLRP3 inflammasome in macrophages. They reported the interesting osteoimmunomodulatory effect of ipriflavone that targets the NLRP3 inflammasome, thus having an anti‐inflammatory effect.…”
Section: The Potential Of the Inflammasome In Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al. ( 2022 ) investigated the early inflammatory response to titanium screws in bone, and concluded that the administration of ipriflavone, a natural isoflavone, decreased the activation of the NLRP3 inflammasome in macrophages. They reported the interesting osteoimmunomodulatory effect of ipriflavone that targets the NLRP3 inflammasome, thus having an anti‐inflammatory effect.…”
Section: The Potential Of the Inflammasome In Immunomodulationmentioning
confidence: 99%
“…They further concluded that the administration of ATP, which is a ligand for NLRP3, leads to the activation of inflammasomes causing the up-regulation of the expression of pro-inflammatory cytokines and accelerates the wound healing. Therefore, identifying molecules that have the ability to modulate the inflammasome assembly and activation, or inflammasome-mediated products, can reduce fibrosis and promote wound healing(Artlett, 2013) Chen et al (2022). investigated the early inflammatory response to titanium screws in bone, and concluded that the administration of ipriflavone, a natural isoflavone, decreased the activation of the NLRP3 inflammasome in macrophages.…”
mentioning
confidence: 99%
“…Additionally, the expression of the NLRP3 inflammasome, which is known to negatively affect bone healing, was also examined. [ 35 ] As shown in Figure A–D, the SP@GCDs (−) group demonstrated the most effective suppression of pro‐inflammatory markers (TNF‐ α, IL‐6, IL‐1β) and NLRP3. Although the SP@GCDs (+) group was not as good as the SP@GCDs (−) group, it still significantly inhibited the expression of TNF‐ α, IL‐6, IL‐1 β, and NLRP3.…”
Section: Resultsmentioning
confidence: 99%
“…Adiponectin, a fat-derived adipokine with anti-diabetic efficacy, can reverse ROS overproduction and alleviate mitochondrial damage by activating AMPK, thus reversing osteoblast impairment and improving the osteointegration (Hu et al, 2017). Chen, Li, Shi et al (2022) revealed that ipriflavone reduced inflammasome activation in macrophages by decreasing mROS and thus ameliorated the host inflammatory response and promoted early bone healing. Resveratrol can also increase mitochondrial biogenesis and reduce mROS and thus improve mitochondrial function (Ma et al, 2017;Ungvari et al, 2011).…”
Section: Mitochondrial Therapeutic Strategies For Improving Implant I...mentioning
confidence: 99%
“…There is a large literature on the roles of mROS in cellular physiological functions, including cell proliferation, migration, and differentiation (Blajszczak & Bonini, 2017;Chen, Li, Shi et al, 2022;Wang, Fu et al, 2021;Wang, Yang et al, 2020).…”
mentioning
confidence: 99%